‘L’Amour aux Antipodes’: Tasma, Australia and the French Connection - Judith Johnston (Cahiers Victoriens et Edouardiens)
Tasma (Jessie Couvreur) wrote and published her best known Australian stories from Europe for a predominantly English and Australian readership. This article investigates Tasma's only known French publication, ‘L'Amour aux Antipodes’ (‘Love in the Antipodes’) which first appeared in August 1880 in the Parisian periodical La Nouvelle Revue, possibly to capitalise on the popularity of a series of lectures on Australia which she had delivered in various French and Belgian cities. I argue that the novella is designed specifically for a French readership, not only in terms of setting, but also because Tasma's usual critique of gender ideology is replaced with a determined anti-clericalism, possibly in response to current debates in Paris at the time and a wish to avoid the fraught gender politics of the Third Republic.